2010
DOI: 10.1158/1541-7786.mcr-09-0546
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell Cycle Genes and Induction of Senescence by Overexpression of OTX2 in Medulloblastoma Cell Lines

Abstract: The transcription factor orthodenticle homeobox 2 (OTX2) has been implicated in the pathogenesis of medulloblastoma, as it is often highly expressed and sometimes amplified in these tumors. Little is known of the downstream pathways regulated by OTX2. We therefore generated MED8A and DAOY medulloblastoma cell lines with doxycycline-inducible OTX2 expression. In both cell lines, OTX2 inhibited proliferation and induced a senescencelike phenotype with senescence-associated β-galactosidase activity. Expression pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 52 publications
7
49
0
Order By: Relevance
“…Identifying the feedback circuits that link the upstream and downstream regulation of this miRNA cluster will be informative. Indeed, there is marked conservation of the upstream regulatory region of the miR-183 cluster and prior ChIP–on-chip analyses have shown enrichment of this promoter region upon immunoprecipitation of the medulloblastoma oncogene, OTX2 [5] (M. Kool, personal communication). At a minimum, incorporation of mTOR inhibitors as a treatment or adjuvant for medulloblastomas expressing miR-183∼96∼182 should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the feedback circuits that link the upstream and downstream regulation of this miRNA cluster will be informative. Indeed, there is marked conservation of the upstream regulatory region of the miR-183 cluster and prior ChIP–on-chip analyses have shown enrichment of this promoter region upon immunoprecipitation of the medulloblastoma oncogene, OTX2 [5] (M. Kool, personal communication). At a minimum, incorporation of mTOR inhibitors as a treatment or adjuvant for medulloblastomas expressing miR-183∼96∼182 should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of OTX2 is low or absent in Shh-driven human medulloblastoma (17,18). OTX2 copy number gain has been associated with more aggressive tumor phenotypes and decreased patient survival (18), and inhibition of OTX2 in medulloblastoma cell lines decreased tumor proliferation and formation in vitro (19). It is currently unclear whether modest upregulation of OTX2 is related to saridegib resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, knockdown by OTX2 siRNA or suppression of OTX2 promoter by 9-cis retinoic acid slowed medulloblastoma tumor growth in mice (5, 19), suggesting that OTX2 expression sustains tumor growth. Recently, Bunt et al reported that induced over-expression of OTX2 in MB cells leads to G1 arrest in cell cycle and senescence-like phenotype (20), while, however, an inducible knockdown of OTX2 activated cell cycle regulators and neuronal genes (21). Beside genomic amplification as a means of OTX2 activation, the majority of medulloblastomas overexpress OTX2 through an unknown mechanism.…”
Section: Introductionmentioning
confidence: 99%